1995
DOI: 10.1007/bf00196402
|View full text |Cite
|
Sign up to set email alerts
|

Sulphide mineralisation in the Olary Block, South Australia

Abstract: The South Australian portion of the Willyama Inliers hosts a diversity of small sulphide and uranium deposits and numerous outcropping gossans. This fact, together with geological similarities to the adjacent Broken Hill Block has led to extensive exploration. A broad classification distinguishes two main types of sulphide mineralisation: 1) stratiform iron sulphide-dominated (+Cu, Zn, Co) deposits which occur widespread within specific stratigraphic intervals, and stratabound occurrences of syn-depositional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…This style of mineralisation, which lacks significant Fe-oxides, has been likened to 'redbed' or stratiform sedimentary Cu (-Co) deposits such as those in the Zambian copper belt and the Kupferschiefer in Europe (Cook & Ashley, 1992). Among the wide range of epigenetic sulfide deposits and occurrences in the Olary Domain (Bierlein et al, 1995) the White Dam Au (-Mo) deposit is distinctive in its lack of iron oxides, syn-deformational quartz-Kfeldspar-plagioclase-biotite vein style, high Au:Cu ratio, and lower stratigraphic position within medium grade metamorphic host rocks, compared to the main Cu-Au-Mo deposits . Molybdenite has yielded Re-Os ages of ~1631 Ma, ~1616 Ma and ~1612 Ma for the White Dam deposit (Fig.…”
Section: Metallogenic Events In the Gawler Craton And Curnamona Provincementioning
confidence: 99%
“…This style of mineralisation, which lacks significant Fe-oxides, has been likened to 'redbed' or stratiform sedimentary Cu (-Co) deposits such as those in the Zambian copper belt and the Kupferschiefer in Europe (Cook & Ashley, 1992). Among the wide range of epigenetic sulfide deposits and occurrences in the Olary Domain (Bierlein et al, 1995) the White Dam Au (-Mo) deposit is distinctive in its lack of iron oxides, syn-deformational quartz-Kfeldspar-plagioclase-biotite vein style, high Au:Cu ratio, and lower stratigraphic position within medium grade metamorphic host rocks, compared to the main Cu-Au-Mo deposits . Molybdenite has yielded Re-Os ages of ~1631 Ma, ~1616 Ma and ~1612 Ma for the White Dam deposit (Fig.…”
Section: Metallogenic Events In the Gawler Craton And Curnamona Provincementioning
confidence: 99%
“…Tongyoung (Yoo et al, 2010) and Cheongyang (Yoo et al, 2006) are mesothermal deposits have similar range to KSO. Orogenic gold deposit from Olary block in South Australia (Bierlein et al, 1995) and Yuryang deposit in Korea (Pak et al, 2005) also shown similar to KSO (Fig. 5.6).…”
Section: Contentsmentioning
confidence: 71%
“…FeS mole % in sphalerite of other deposits; for example, Pongkor in Indonesia (Warmada et al, 2003) has value 0.1 to 2.0 mole %, Central Khamchatka in Russia (Andreeva et al, 2013) has value around 0.0 to 3.0 mole %, Tongyoung in Korea (Yoo et al, 2010) has 6.2 to 13.8 mole %, Cheongyang in Korea (Yoo et al, 2006) has 5.9 to 8.3 mole %, Yuryang deposit in Korea (Pak et al, 2005) has 11.0 to 17.6 mole %, Olary block in South Australia (Bierlein et al, 1995) has 3.8 to 18.7 mole %.…”
Section: Contentsmentioning
confidence: 99%